China's meat and grain imports during 2000–2012 and beyond: A comparative perspective - Wu-sheng YU; Li-juan CAO (Journal of Integrative Agriculture)
This paper provides a review on China's meat trade for the 2000–2012 period and discusses its future development, with reference to China's grain trade. With marginal decreases in meat exports and slight increases in their imports, China's net imports of major meat products (including pork, beef, mutton and poultry but excluding meat offal) were just below 1 million tons in 2012, dwarfed by China's net imports of grains which reached 66.7 million tons in the same year. This slow growth in meat trade seems to contradict earlier expectations on increasing meat demand and imports, based upon projected shifts in consumption patterns driven by rapid per capita income growth. Several plausible explanations of this paradoxical trade pattern are offered, including mass imports of feed grains, persistent (but shrinking) gaps between Chinese and international meat prices, tariff barriers, and non-tariff measures. In the near future China may not be able to maintain such a lower profile on the world meat markets, as per capita income is projected to continue to rise and domestic production cost advantages erode due to rising labor costs. A model-based projection exercise indicates that under plausible assumptions China's meat imports may rise sharply by 2030.